The Influence of @musuem.benteng.vredeburg’s TikTok Content Attractiveness Toward Followers’ Visiting Interest - Mandiri, Ilming; Nuur Rasyid , Haryadi Arief (Jogjakarta Communication Conference (JCC), 2025)
This study explores how the attractiveness of TikTok content on the @museum.benteng.vredeburg account influences followers' interest in visiting the museum. The research used a quantitative explanatory method by distributing questionnaires to 366 respondents selected through convenience sampling. The analysis was carried out using simple linear regression. The test results show an influence between the dependent and independent variables at 49.1%. This study proves that the attractiveness of TikTok content @museum.benteng.vredeburg affects followers' interest in visiting.